2011
DOI: 10.2215/cjn.00580110
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatinine Levels Are Significantly Influenced by Renal Size in the Normal Pediatric Population

Abstract: SummaryBackground and objectives Clinical and experimental data have shown that differences in nephron endowment result in differences in renal mass and predisposition to chronic renal failure, hypertension, and proteinuria. We hypothesized that a significant proportion of the variance in GFR, as estimated by serum creatinine, is attributable to differences in renal size in normal children.Design, setting, participants, & measurements A total of 1748 normal renal ultrasounds that were performed in children old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…23 In line with that study, we observed an inverse association of fetal kidney size with creatinine and cystatin C levels in childhood, and a positive association with eGFR. We previously observed that small fetal kidney size tends to track throughout early childhood.…”
Section: Discussionsupporting
confidence: 90%
“…23 In line with that study, we observed an inverse association of fetal kidney size with creatinine and cystatin C levels in childhood, and a positive association with eGFR. We previously observed that small fetal kidney size tends to track throughout early childhood.…”
Section: Discussionsupporting
confidence: 90%
“…It is estimated that for every 1-kg increase in birth weight, glomeruli number increases by approximately 260,000 [7, 34]. Reduced nephron number is associated with compensatory mechanisms including glomerular hyperfiltration, which can ultimately lead to CKD; this process is exacerbated by hypertension [35, 36]. Potential mechanisms for the reduction in nephron number during gestation include alterations in DNA methylation, increased apoptosis in the developing kidney, renin-angiotensin system alterations, vitamin A and other nutritional deficiencies, and increased fetal glucocorticoid exposure [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 1 748 healthy children over 6 months of age established a close correlation between renal length and thickness, and creatinine [74]. Abitbol et al [75 && ] studied CysC, creatinine, and renal volume in premature neonates and concluded that CysC was a better marker of neonatal GFR.…”
Section: Can We Use the Renal Volume As Marker Of Glomerular Filtratimentioning
confidence: 99%